RANCANG BANGUN APLIKASI PENJUALAN SAYUR BERBASIS WEB UNTUK MENDUKUNG KESEJAHTERAAN PEDAGANG - Riski Annisa; Arvin Hidayat Waluya (Politeknik Bisnis Indonesia, 2021)
Along with the development of the times, the development of technology has also developed rapidly. The development in the field of information and communication technology at this time has brought very important benefits for the advancement of human life. Various business programs can be developed into a system whose performance uses a computer or mobile device, and one of these programs is that it can publish information on an item that is sold via the internet or using a web-based system. Many housewives find it difficult or lazy to shop for vegetables because of the full queues to shop at the local vegetable shop, busy with office matters or taking care of children and other activities. Therefore an application was made that can help save time and can also help small vegetable and fruit entrepreneurs to sell their products in applications that have been made. In the application that has been made, a buyer can buy a variety of fresh vegetables and fruit of guaranteed quality and for the admin section. Admins can change web page settings by simply going to the admin page section to manage the display of all displays that are on the main web section.